Anti-interference monitoring of sweat pH: a new sensing mechanism based on the p–n transition potential of a flexible Bi2O3 photoelectrode. Issue 6 (2nd February 2023) - Dong, Boheng; Zhang, Xinya; Cao, Lingfeng; Jiang, Xiang; Wang, Fuxian
Abstract : p–n transition potential ( V p–n ) as a new signal for photoelectrochemical (PEC) sensors. V p–n based flexible wearable PEC pH sensor shows strong anti-interference ability. A benchmark signal-to-noise ratio of 10 6 was achieved during practical exercise. Abstract : The anti-interference capability is vital for flexible wearable sensors, especially for detection during exercise. Herein, we propose a new sensing strategy based on the p–n transition potential ( V p–n ) of the Bi2 O3 photoelectrode. The V p–n decreases linearly with pH and more importantly it demonstrates strong anti-interference performance against the change in the coverage of sweat on the photoelectrode, the variation in light intensity, and the bend of the photoelectrode. Moreover, the Bi2 O3 photoelectrode shows good flexibility and biocompatibility, based on which a pH monitor that can interact with a smartphone is developed, enabling convenient and accurate monitoring of sweat pH during practical exercise. The monitor exhibits a benchmark signal-to-noise ratio that is one order of magnitude higher than that of the state of the art pH monitors. The strategy of using the V p–n signal of a semiconductor for pH sensing is proposed for the first time, which opens a new avenue for designing anti-interference wearable sensors.